Exploratory study of qualitative psychological factors influencing performance in esports - Papp, Dávid; Burján, Réka; Csukonyi, Csilla (Frontiers in Sports and Active Living, 2025)
IntroductionA comprehensive understanding of the psychological characteristics underlying performance in esports is key to the effectiveness of sport psychology work. In the present research, we aimed to identify the psychological factors that influence the performance of e-athletes and to confirm the results of previous research on specific characteristics.MethodsThe study used a qualitative method consisting of focus group discussions (N = 15) and semi-structured interviews (N = 30). We applied content analysis using Atlas.ti content analysis software with the assistance of three independent coders.ResultsThe results suggest that the most significant characteristic behind the performance of e-athletes is their resilience and resilient personality. In addition, generalisable traits such as stress tolerance and sustained attention also had high-frequency values. However, some characteristics are specific to the eSport genre as well as to the particular eSport title of individual or team esports with varying emphasis on such things as cooperation and communication skills. The characteristics used in the analysis were classified into six groups of competencies.DiscussionFinally, as a result of the research, it was possible to identify characteristics and classify them into competencies, which can serve as a reference point in the field of selection and talent management and can also serve as a basis for the development of psychodiagnostic measurements and tests for e-athletes in the future.